Creating customer connections : how to make customer service a profit center for your company - Burke, Jack, 1950- (Taking control series., 1997)
Martin Bury, after a 40-Ưyear career as an automobile dealer, described his experiences in the book "The Automobile Dealer." Analyzing lost customers, Bury arrived at some statistics that could open the eyes of a marketer or customer service person from any industry. Over a four-Ưyear period, here are the reasons businesses lose their customers: one percent will die; three percent will move out of the area; five percent will be lured away by other salespeople; nine percent will be lured away by lower prices; fourteen percent will leave because of unresolved complaints; sixty-Ưeight percent will leave because of poor service, discourteous treatment or indifference. The moral to these statistics: providing courteous, helpful service can cut client losses by more than twoƯthirds. But good customer service is not good enough. Customer satisfaction is not--by itself--enough. Success in business requires an integrated marketing and communication approach that will result in the cultivation of a nexus between a company and its customers. This book is written to help you build that nexus between your company and your customers